Demonstrasi Senam Ibu Hamil sebagai Upaya Persiapan Persalinan di Posyandu Al Khoeriyah Dukuh Bulakwungu Desa Benda - Himatul Khoeroh; Naila Qotrunnada; Nilamayuli Maula; Novrian Salwa; Putri Marsanda; Siti Alma Rahmah (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Pregnancy exercise is physical exercise with certain movements carried out specifically to improve maternal health during pregnancy. Objective: Demonstrate pregnancy exercise movements in preparation for childbirth through demonstrations. Method: Te method used in community service is in the from of a class for pregnant women in the from of a pregnancy exercise demostration. Results: The results of the evalution carried out from 8 pregnant women praticipants, three were 20% of pregnant women with TM I as increasing their knowledge to face the next trimester, and the remaining 60% were TM III who had done pregnancy exercises well and enthusiastically. Discussion: Contains a description of the discussion of community service result, theoretical discussions relevant to the findings of community service result. Also discusses theoretical findings from the service process from the beginning until social change occurs. Conclusion: That pregnant women can pratice pregnancy exercises correctly and pay more attention to preparation for childbirth. Apart from that, pregnant women have also gained knowledge to face the next trimester.